Risk factors and evolution of Ventilator-associated pneumonia by Staphylococcus aureus sensitive or resistant to oxacillin in patients at the intensive care unit of a Brazilian University Hospital - Moreira,Michel R. (2008)
This study investigated the participation and risk factors of VAP by resistant (ORSA) or sensitive (OSSA) S. aureus to oxacillin and evaluated the implications of adequate or inadequate empirical antimicrobial therapeutics in its evolution in patients interned in a mixing ICU of adults. A patient control-case study with PAVs by ORSA and OSSA was carried out from May 2005 to April 2007 involving 993 patients. VAP was defined based on clinical, radiological, and microbiological (> 106 CFU/mL count in the tracheal aspirate) criteria. Four hundred and seventy four (47.7%) patients were submitted to mechanical ventilation with 141 (29.7%) VAPs, with S. aureus as the most frequent agent (41.2%). The phenotype ORSA accounted for 47.5% and OSSA for 52.5%, predominant in late-onset VAPs with frequencies of 93.1% and 68.7%, respectively. Age > 60, use of corticoid and previous antibiotic therapy were related (p<0.05) with the development of VAP by ORSA. Mortality rate was higher (p>0.05) in the group with VAP by ORSA (37.9%). S. aureus was the main agent of VAPs, around half by ORSA, associated with age, late-onset VAP development and previous use of antibiotics and corticoids, but with no significant difference in mortality compared with VAP by OSSA.